2018
DOI: 10.1016/j.avsg.2017.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and Design of the ARREST Trial Investigating Mesenchymal Stem Cells in the Treatment of Small Abdominal Aortic Aneurysm

Abstract: ARREST will be pivotal in assessing the safety of MSC infusion and provide preliminary data on the ability of MSCs to favorably modulate the pathogenic AAA host immune response. The data gleaned from this phase I trial will provide the groundwork for a larger, phase III RCT which may provide the first pharmaceutical intervention for AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
1
18
0
1
Order By: Relevance
“…Indeed, it has been demonstrated that the administration of MSCs‐CM was as effective as MSC treatment itself in various diseases . Recently, MSCs have been shown to prevent AA formation and progression in a variety of AA models . In the present study, we investigated the effects and mechanisms of the administration of MSCs‐CM on AngII‐induced AA in apoE −/− mice.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, it has been demonstrated that the administration of MSCs‐CM was as effective as MSC treatment itself in various diseases . Recently, MSCs have been shown to prevent AA formation and progression in a variety of AA models . In the present study, we investigated the effects and mechanisms of the administration of MSCs‐CM on AngII‐induced AA in apoE −/− mice.…”
Section: Discussionmentioning
confidence: 94%
“…14,15,17 Recently, MSCs have been shown to prevent AA formation and progression in a variety of AA models. [10][11][12]25 In the present study, we investigated the effects and Macrophages are essential mediators of the inflammatory response and play an important role in inflammation-associated diseases. Previous studies have suggested that macrophage polarization may be involved in the development of AA.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to studies with local implantation of MSCs [ 15 , 20 ], intravenous injection of MSCs represents the minimum invasive systematic route for cellular therapy, and has been previously shown to be effective in different AAA models [ 16 , 18 , 34 ]. In addition, a randomized controlled trail investigating MSCs in small human AAA also applied intravenous administration [ 58 ], which further arise the clinical convenience and feasibility of intravenous administration.…”
Section: Discussionmentioning
confidence: 99%
“…This antigen-specific regulatory T lymphocyte primarily elaborates IL-10, a potent anti-inflammatory cytokine in response to antigen recognition. 9 Not only was this Tr1 population depleted, but it was also less functional in terms of ability to migrate to a stimulus, secrete IL-10 when activated, and polarize monocytes toward the anti-inflammatory M2 macrophage. Therefore, we hypothesized that this deficit of IL-10 and Tr1, and inability control aortic wall inflammation, may be the driver for initial aortic ectasia and eventual aneurysm formation.…”
Section: Circulation Research March 30 2018mentioning
confidence: 99%
“…9 These potential participants are identified through US Preventative Task Force-recommended AAA sonographic screenings for patients aged 65 years, an examination provided for no cost as a part of the Welcome to Medicare package. In this study, 36 patients are randomized at a 1:1:1 ratio to placebo, 1×10 6 MSCs/kg, or 3×10 6 MSCs/kg through a large bore peripheral IV and followed for 5 years to determine changes in aortic diameter, cytokine expression, and circulating immune cell expression.…”
Section: Circulation Research March 30 2018mentioning
confidence: 99%